(untitled) (Applied Sciences in Dentistry, 2026)
Objectives: To evaluate dental students’ perceptions of learning, self-efficacy, and limitations when using three different anatomical study tools: 3D printed models, 2D visualizations, and 3D visualizations in the study of the sphenoid bone. Materials and Methods: A descriptive methodology was employed with 38 dental students from an Anatomy I course. Participants were randomly assigned to use one of the three study tools. Data was collected through a validated survey assessing satisfaction with learning, self-efficacy, and perceived limitations. Statistical analysis included Pearson’s correlation coefficient to explore associations between variables. Results: Students showed higher satisfaction and self-efficacy with 3D printed models and 3D visualizations compared to 2D images. However, 2D images were perceived as more manageable, likely due to anatomical labels. A moderate positive correlation was found between satisfaction and self-efficacy (r = 0.576, p < 0.001). No significant correlations were observed between perceived limitations and academic performance. Conclusions: The integration of 3D technologies in anatomical education enhances student satisfaction and perceived self-efficacy. However, the accessibility and cost of 3D printed models present challenges for widespread adoption. Future educational strategies should consider 3D visualizations with digital labeling to optimize learning experiences.